A First Look at Early Intervention and Early Childhood Providers' Reports of Assistive Technology Reuse. Issue 3 (September 2013) - Wilcox, M. Jeanne; Campbell, Philippa H.; Fortunato, Livia; Hoffman, Jill
Reports of the experiences of 256 early intervention and early childhood providers with assistive technology (AT) reuse were obtained via a national online survey. A majority of providers (75.7%) indicated that they had never donated, sold, or received a device from a formal AT reuse program. However, a majority did report reusing AT devices within their own programs, indicating that reuse was occurring at a program-based level. Limitations of program-based reuse are discussed and suggestions are made for expanding the capacity and usability of reuse through affiliations with statewide and regional networks. In addition, respondent data suggest an expansion of AT reuse beyond devices, to include ideas and instructions for low-tech solutions to meet the needs of younger children in particular.